2018
DOI: 10.2478/ama-2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

Constructional Features of Ropes in Functional Units of Mining Shaft Hoist

Abstract: In this paper structural analysis of steel ropes applied in mining shaft hoists was conducted. Functions of the ropes which they fulfilled in these shaft hoists were identified. Expected operational features of ropes were indicated too. An analysis was carried out four identified groups of ropes: hoisting ropes, balance ropes, leading rope and fender ropes. Basic constructional features: geometrical and material of ropes, which they should be characterized in each of mentioned functional groups were indicated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…It should be emphasized that determination of a set of the most significant assessment criteria to be used for identification of significant characteristics consistent with the accepted criteria and establishing their significance is an important task for determination of a given system functioning quality assessment [2][3].…”
Section: Introductionmentioning
confidence: 99%
“…It should be emphasized that determination of a set of the most significant assessment criteria to be used for identification of significant characteristics consistent with the accepted criteria and establishing their significance is an important task for determination of a given system functioning quality assessment [2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Each technical object has a set of functional qualities, such as: reliability, wear resistance, fatigue strength, resistance to movement, corrosion resistance, etc. Based on numerous studies, it may be concluded that these characteristics depend on the greatest extend of the condition of the surface layer, especially on the parameters characterizing the geometric surface structure [1][2][3][4][5][6][7][8]. Due to the fact that most these damages happen inside of the surface layer, the proprieties enlarging-resistance on destructive working extortions during machine and devices operation are given rught to the layer.…”
Section: Introductionmentioning
confidence: 99%
“…Steel ropes are complex flexible structures used in many technical applications, such as elevators [1], crane [2,3,4], marine applications [5], cable ways and hoisting mine applications [6,7]. In many high-rise residential buildings or multistorey warehouses, machinery, so called lifts, are used for the vertical transportation of people or weights between attitudinally distant places [8].…”
Section: Introductionmentioning
confidence: 99%